Growth regulation mechanism of Rhododendron moulmainense to high-temperature stress: integrated physiological, transcriptomic, and metabolomic insights - Khan, Zaid; Liu, Sijia; Peng, Jingen; Cai, Hongyue; Bai, Yuqing; Hu, Bing; Zhang, Luwen; Zhuang, Peng; Cai, Zipeng; Xie, Lijuan (Frontiers in Plant Science, 2025)
Rhododendrons domestication in urban habitats is limited due to their vulnerability to higher air temperatures, and their adaptive mechanisms are poorly understood. In this study, we evaluated the growth response and regulatory mechanisms of Rhododendron moulmainense to high-temperature stress of T35 (35°C) and T42 (42°C). The findings demonstrated that high-temperature stress decreased chlorophyll fluorescence and contents, which was validated by the damaged chloroplast structure in transmission electron microscopy. Scanning electron microscopy resulted in reduced leaf stomatal traits, altering gas exchange, and thus, photosynthetic rates were decreased. High-temperature or heat stress (HT) increased the activities of antioxidants and osmolytes under T42 to counteract the damage of reactive oxygen species (ROS). Transcriptome and metabolome analysis using Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment upregulated 9 differentially expressed genes (DEGs) out of 16 and 9 differentially accumulated metabolites (DAMs) out of 10 of the starch-sucrose metabolism pathway and 11 DEGs out of 16 and 9 DAMs out of 13 of ABC transporters metabolism under high-temperature stress of 42°C to reveal the synergistic effects of these pathways. HT induced expression of genes and metabolites in the starch-sucrose metabolism pathway, which likely increased the photosynthesis and sugar metabolism enzymes such as Rubisco, citrate synthase, sucrose synthase, and sucrose phosphate synthetase. The findings revealed that DEGs and DAMs regulating secondary metabolites (SM) in starch-sucrose metabolism, encoding SUS, TPS1, BAM1, sucrose, D-ribose, and D-fructose, and ABC transporters such as ABCC1, ABCC2, ABCG2, Thiamine, and Betaine were significantly higher in T42 to regulate the plant growth under HT. These results imply that the interconnected pathways of starch-sucrose metabolism and ABC transporters may help us better understand the growth regulation and domestication processes of Rhododendron under high-temperature stress scenarios.